A STUDY ON VISUAL LIMITATION OF AGE, NUMERICAL SIZE, AND EXPOSURE TIME WHILE USERS OPERATE MOBILE DEVICES. - PO-CHAN YEH (Perceptual & Motor Skills, 2015)
Technological advances have driven the development of information technology (IT) products and communication using mobile devices has become a part of daily life. When using mobile devices, reading time and font size are important communication elements that significantly affect reading performance. However, studies of reading performance in older samples have mainly used printed material or computer monitors; this study examined the performance of users when reading text messages on the interfaces of mobile devices and described their visual limitations. Sixty-two participants took part in the experiment, which involved displaying different font sizes and exposure times. The younger group read 10-point font accurately, while the older group had much worse accuracy, even at 14 points. The younger group correctly read text messages displayed for 0.4 sec. above 80% of the time, while the older group's accuracy was severely impaired even when text was displayed for 1 sec.